PSYCHOLOGICAL EFFECTS AND COLOR THERAPY OF COLORS: रंगों का मनोवैज्ञानिक प्रभाव एवम् रंग चिकित्सा - GUPTA, SAKSHI (International Journal of Research -GRANTHAALAYAH, 2014)
Every person in the world adopts some medium to express inner feelings. For some, voice is the medium, for some, but for a painter, color is the medium or means to express his feelings. Expresses the emotions emitted in the mind through various tones of color. Taking full care of the combination methods in the pictures, he uses darker or sharper colors and lighter and lighter colors elsewhere. He gets self-satisfaction by expressing his feelings through this method. A work reveals many dimensions hidden within it. No matter how many different angles an artist has made her, but she is presented in a different form and meaning in front of the audience, this is its power and talent. For an artist, color is an important part of his work. That entire nature reveals this entire world through different colors. संसार में प्रत्येक व्यक्ति अन्तर्मन के भावों को व्यक्त करने के लिये किसी न किसी माध्यम को अपनाता है। किसी के लिये स्वर माध्यम हैं तो किसी के लिये शब्द परन्तु एक चित्रकार के लिये उसके भावों को अभिव्यक्त करने का माध्यम या साधन रंग है। रंगों की विभिन्न तानों के द्वारा मन में उद्वेलित भावों को अभिव्यक्त करता है। वह चित्रों में संयोजन विधियों का पूर्ण ध्यान रखते हुये कहीं गहरे या तीखे रंगों का प्रयोग करता है तो कहीं हल्के व कोमल रंगों का। इस विधि से अपने भावों की अभिव्यक्ति करके उसे आत्म-संतोष मिलता है। एक कृति अपने भीतर छुपे हुये अनेक आयामों को उद्घाटित करती है। एक कलाकार ने उसे कितने ही भिन्न दृष्टि कोण से बनाया हो परन्तु दर्षक के सम्मुख वह एक भिन्न रूप व अर्थ में प्रस्तुत होती है, यही इसकी शक्ति व प्रतिभा है। एक कलाकार के लिये रंग उसकी कृति का महत्वपूर्ण अंग है। वह समूची प्रकृति इस सम्पूर्ण विष्व को विभिन्न रंगों के माध्यम से ही उद्घाटित करता है।